O MARCO LEGAL DAS ENERGIAS SOLAR, EÓLICA E DE BIOGÁS NO BRASIL: AVANÇOS E PERSPECTIVAS (CIPEEX, 2026)
Brazil occupies a prominent position in the global renewable energy landscape, with an electricity mix comprised of 88.2% sustainable sources in 2025, significantly exceeding the global average of 30%. This outlook is the result of decades of structuring public policies and innovative regulatory frameworks that favor the development of sustainable technologies. The objective of this study is to analyze the Brazilian legislative landscape for renewable energy, focusing on the regulatory frameworks for solar photovoltaic, wind, and biogas sources, identifying regulatory developments and sectoral perspectives. The study was conducted through documentary and bibliographical research, with a systematic analysis of federal and state legislation, regulatory agency resolutions, technical standards, and official statistical data from the 2012-2025 period. A qualitative and quantitative approach was used, with an interpretative synthesis of the legal frameworks. Structural milestones were identified, such as Law 14,300/2022 (distributed generation), Law 15,097/2025 (offshore wind), and Law 13,576/2017 (RenovaBio). The country consolidated its position as the world's fifth-largest wind power (33 GW), surpassed 64 GW in solar photovoltaic generation, and expanded its biogas potential to 84 billion Nm³ per year. Asymmetries in state tax incentives and a need for regulatory harmonization were identified. Brazil has a robust legislative framework for renewable energy, positioning itself at the forefront of the global energy transition. Future success will depend on maintaining consistent policies, investing in infrastructure, and greater integration between federal and state frameworks.
Keywords: Energias renováveis; Política energética; Brasil; Sustentabilidade